Consumer benefits from increased competition in shopping outlets measuring the effect of Wal-Mart - Hausman, Jerry A. 1946-; Leibtag, Ephraim (National Bureau of Economic Research, 2005)
"Consumers often benefit from increased competition in differentiated product settings. In this paper we consider consumer benefits from increased competition in a differentiated product setting: the spread of non-traditional retail outlets. In this paper we estimate consumer benefits from supercenter entry and expansion into markets for food. We estimate a discrete choice model for household shopping choice of supercenters and traditional outlets for food. We have panel data for households so we can follow their shopping patterns over time and allow for a fixed effect in their shopping behavior. We find the benefits to be substantial, both in terms of food expenditure and in terms of overall consumer expenditure. Low income households benefit the most"--National Bureau of Economic Research web site.
Keywords: Wal-Mart (Firm); Retail trade -- United States; USA